2015
DOI: 10.1111/1462-2920.12708
|View full text |Cite
|
Sign up to set email alerts
|

Seeing is believing: novel imaging techniques help clarify microbial nanowire structure and function

Abstract: SummaryNovel imaging approaches have recently helped to clarify the properties of 'microbial nanowires'. Geobacter sulfurreducens pili are actual wires. They possess metallic-like conductivity, which can be attributed to overlapping pi-pi orbitals of key aromatic amino acids. Electrostatic force microscopy recently confirmed charge propagation along the pili, in a manner similar to carbon nanotubes. The pili are essential for long-range electron transport to insoluble electron acceptors and interspecies electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
70
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 84 publications
(74 citation statements)
references
References 70 publications
3
70
0
1
Order By: Relevance
“…As previously noted in the analysis of the Geobacter sulfurreducens PilA sequence (Malvankar et al, 2015;Reardon & Mueller, 2013;Reguera et al, 2005), the N-termini of the epilin proteins share many similarities with previously described type IVa PilA found in members of genera such as Neisseria, Pseudomonas, Escherichia and Myxococcus (Giltner et al, 2012;Mattick, 2002). It is highly conserved and consists of one or two alpha helices and a transmembrane *Secondary structure predictions were made with the Jnet algorithm (Cuff & Barton, 2000) on the Jpred4 server ( (Drozdetskiy et al, 2015) Geobacter uraniireducens…”
Section: Resultsmentioning
confidence: 75%
See 3 more Smart Citations
“…As previously noted in the analysis of the Geobacter sulfurreducens PilA sequence (Malvankar et al, 2015;Reardon & Mueller, 2013;Reguera et al, 2005), the N-termini of the epilin proteins share many similarities with previously described type IVa PilA found in members of genera such as Neisseria, Pseudomonas, Escherichia and Myxococcus (Giltner et al, 2012;Mattick, 2002). It is highly conserved and consists of one or two alpha helices and a transmembrane *Secondary structure predictions were made with the Jnet algorithm (Cuff & Barton, 2000) on the Jpred4 server ( (Drozdetskiy et al, 2015) Geobacter uraniireducens…”
Section: Resultsmentioning
confidence: 75%
“…Analysis of the structure of the Geobacter sulfurreducens e-pilus suggested that the lack of this C-terminus sequence permits the pilin monomers to pack more tightly than the larger pilin monomers found in most bacteria, yielding a thinner pilus diameter and positioning amino acids in patterns that confer conductivity (Malvankar et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There is debate whether the aromatic amino acids contribute to a traditional electron-hopping electron transport mechanism or whether over-lapping π-π orbitals of the aromatics confer a metallic-like conductivity similar to that observed in synthetic conducting polymers (Lampa-Pastirk et al 2016, Lovley and Malvankar 2015, Vargas et al 2013. However, the uncertainty over these mechanistic details should not obscure the fact that long-range electron transport via epili is a remarkable strategy for long-range biological electron transfer.…”
mentioning
confidence: 99%